Effect of a primer containing Artemisinin on dentin endogenous MMPs and resin bond durability. (April 2023) - Ding, Yashuang; Li, Qiongfang; Tang, Wenya; Pan, Yahui; Nie, Rongrong; Meng, Xiangfeng
Abstract: Objectives: This study aims to investigate the potential effect of a primer containing Artemisinin (ART) or its derivative—dihydroartemisinin (DHA) on the dentin endogenous MMPs activity and resin bonding durability under etch-and-rinse mode. Materials and methods: Molecular docking was applied for evaluating the potential interactions of MMP-2 and MMP-9 with ART and DHA. Then human third molars were randomly assigned to six groups, after etch-and-rinse treatment, pretreated with the primers containing 0.25, 0.5 mg/mL ART, 0.25, 0.5 mg/mL DHA and 2% chlorhexidine (CHX) for 2 min, respectively, while one untreated group was served as the control group. The endogenous MMPs activity of demineralized dentin was tested with in situ zymography test and zymographic assay. Following the etch-and-rinse bonding process with a universal resin bond, the specimens of the microtensile bond strength (μTBS) and nanoleakage were tested with or without 10, 000 °C thermocycling and 6-month storage in artificial saliva at 37 °C. Results: Molecular docking showed that ART and DHA combined with MMP-2 and MMP-9 through forming covalent bonds with the zinc ion of MMPs. Compared with the control group, the ART, DHA and CHX groups showed less endogenous MMPs activity, and the MMPs activity of 0.5 mg/mL DHA group had no significant difference from that of 2% CHX group. Ageing condition reduced the μTBS values dramatically and also aggravated the nanoleakage of all the groups, specifically, the control group showed lower μTBS value and a broader, thicker and more consecutive silver deposition than other groups. Conclusions: The primer containing ART or DHA could preserve bond durability and slow down the nanoleakage of resin-dentin interface over time through inhibiting the endogenous MMPs activity.